Elements of creativity in academic drawing Holovatyi S.S. (Pedagogy of Higher and Secondary Education, 2006)
In the article an author denies the simplified or distorted use of concept „creative approach" in educational practice, which at times grows into similarity something stylish and modern in today's professional teaching. Illogicality of contrasting of creation to teaching is proved m the offered material, because the last teaches to the artistic language, which creation will be realised by.
Keywords: graphic letter; figure; tone; form; creative component